Ustekinumab in Crohn's disease: Real‐world outcomes from the Sicilian network for inflammatory bowel diseases. Issue 3 (2nd February 2021) - Viola, Anna; Muscianisi, Marco; Macaluso, Fabio S; Ventimiglia, Marco; Cappello, Maria; Privitera, Antonino C; Magnano, Antonio; Pluchino, Dario; Magrì, Giovanni; Ferracane, Concetta; Mocciaro, Filippo; Garufi, Serena; et al.
Abstract: Background and Aim: Ustekinumab is approved in Europe for the treatment of moderate to severe Crohn's disease (CD). Italian real‐life data are scarce, so the aim of this study was to assess the effectiveness and safety of ustekinumab in an Italian cohort of CD patients. Methods: Data of patients with CD who started using ustekinumab were extracted from the cohort of the Sicilian Network for Inflammatory Bowel Disease. Primary end‐points were steroid‐free clinical remission at 8, 24, and 52 weeks of therapy and reduction of C‐reactive protein. Secondary end‐points were treatment response, treatment persistence at 12 months, and safety. Results: A total of 131 patients (males 56%; mean age 46 years ± 15) were included. All patients were biologics experienced except for one. At 24 and 52 weeks, 40% and 43% of patients achieved steroid‐free clinical remission, and 64% and 62% had clinical response, respectively. At the end of follow‐up, there was a significant reduction of steroid use ( P = 0.012) and of the Harvey‐Bradshaw Index ( P = 0.001). The probability of persistence in therapy with ustekinumab after 12 months of treatment was 89%. The only factor associated with discontinuation was older age. Conclusions: Data from our real‐life cohort of treatment‐refractory CD patients suggest the satisfactory effectiveness and safety profile of ustekinumab. Abstract : We assessed one‐year effectiveness and safety of ustekinumab in an real‐life cohort of treatment‐refractory CD patients. At 52 weeks 43% of patients achieved steroid‐free clinical remission and 62% had clinical response with a persistence in therapy of 98% and a significant reduction of steroid use ( p  = 0.012) and of HBI ( p  = 0.001). Data from our cohort suggest satisfactory effectiveness and safety profile of ustekinumab.